Women and Modernity in Malay Television Drama: A Case Study of ’Azlina" - Shakila Manan (Wacana Seni Journal of Arts Discourse, 2003)
The year 1991 saw the unveiling of Prime Minister Mahathir's plan to transform Malaysia into a fully developed country by the year 2020. This grand plan, or Vision 2020, soon became the catch phrase of the 90's, one thet the media were quick to promote and publicise via patriotic songs aired during prime time viewing and via certain television programmes. Vision 2020 is also Mahathir's modernity project as it provides the push towards greater economic prosperity, the adoption and celebration of Western technology and modern lifestyle. A move towards modern lifestyle is not without problems. For there are bound to be contestations and conflicts, especially where women are concerned, as it requires substantive changes in roles, status and functions of women.